Spectral analysis of Fourier transform mass spectrometry data - Imanuel, Denny (2008)
Sequential FFT algorithms are investigated and extended, some Parallel FFT algorithms are discussed, as well as several Peak and Gulch Detection (PGD) algorithms for mass spectrum data are developed. The whole research includes the implementation of these various algorithms into MatLab for computer simulation.